2002
DOI: 10.1034/j.1600-0420.2002.800506.x
|View full text |Cite
|
Sign up to set email alerts
|

The capillary blood flow in ischaemic type central retinal vein occlusion: the effect of laser photocoagulation

Abstract: ABSTRACT. Purpose: To determine the effect of photocoagulation on retinal blood flow (RBF) in eyes with ischaemic type central retinal vein occlusion (CRVO). Patients and Methods:Retinal blood flow was measured in 12 eyes with CRVO, 12 fellow eyes and 12 eyes of 12 age-matched healthy subjects using the Heidelberg retinal flowmeter (HRF). Microvascular blood flow values (volume, flow, velocity) were recorded from the upper temporal retina and macula. Eyes were re-examined 1 month after photocoagulation. We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
(23 reference statements)
0
14
0
1
Order By: Relevance
“…With these transparencies, the 10 ϫ 10-pixel measurement window of the HRF was placed at the same location on consecutive flow images. Local flow (LF) was calculated in two ways: as the median 53 and the mean 47,55,56,[61][62][63] of the 100 pixel values within the measurement window of the HRF. The median was calculated, as it has been shown that this method provides a better description of the central tendency of the pixel values within the measurement window in HRF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With these transparencies, the 10 ϫ 10-pixel measurement window of the HRF was placed at the same location on consecutive flow images. Local flow (LF) was calculated in two ways: as the median 53 and the mean 47,55,56,[61][62][63] of the 100 pixel values within the measurement window of the HRF. The median was calculated, as it has been shown that this method provides a better description of the central tendency of the pixel values within the measurement window in HRF.…”
Section: Methodsmentioning
confidence: 99%
“…53 The mean of the 100-pixel window was calculated, as this is the most common method by which to analyze flow when using the HRF. 47,55,56,[61][62][63] The mean BF within the neuroretinal rim (mean rim flow, MRF) was measured with the automatic full-field perfusion image analyzer (AFFPIA). 64 The area of cupping defined in HRT images was applied as a guide to reproduce the size and the location of the cupping on the HRF images accurately when analyzing them with the AFFPIA software.…”
Section: Methodsmentioning
confidence: 99%
“…Collateral capacity in symptomatic cases obviously does not suffice to ward off an increase in retinal venous pressure, venous dilation, retinal haemorrhage, retinal oedema and the occasional optic disc oedema. Studies have shown a reduction in retinal venous blood flow velocity using colour Doppler flowmetry,2 3 a reduction in capillary blood flow velocity on the Heidelberg retinal flow meter4 and an increased arteriovenous passage time on fluorescein and indocyanine green angiographies 5–7. Reduction of blood flow leads to retinal hypoxia8–10 and upregulation of vascular endothelial growth factor (VEGF),11 12 which would lead to vasodilation and hyperperfusion 13.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted in this context, however, that eyes with ischaemic CRVO, if left untreated, usually undergo PRP more often to increase retinal blood flow, which however does not seem to have an effect on the perfusion of the compromised macula (Arvas et al. 2002).…”
Section: Summary Of the Resultsmentioning
confidence: 99%